Rola i zadania Służby Celnej w systemie bezpieczeństwa publicznego i przeciwdziałaniu terroryzmowi - Staniów, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article examines the role and tasks of the Customs Service in the public security system and combating terrorism. Given the increasing globalisation of social and economic processes, in modern societies the question of ensuring security and maximum protection of the social order does not concern just one agency — even if it is exceptionally well-equipped and competent. The constantly growing economic freedom and constitutional guarantees of civil rights force state administrations — faced with a radicalisation of terrorist groups — to built a system of safeguards based on cooperation of various agencies and efficient information exchange between them. One of such agencies is the Customs Service. It contributes to the state protection system, influencing the level of citizen security. As a protection-focused institution, the Customs Service may also use physical coercion and firearms. The head of the Customs Service is a permanent member of the Task Force for Combating Terrorist Threats.
Keywords: Służba Celna; terroryzm; bezpieczeństwo narodowe; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa